Testes de vigor em sementes de milho - Peres, Willyder Leandro Rocha [UNESP] (2009)
The objective of this work was to compare the standard germination and several vigor ( first count, accelerated aging, electrical conductivity, cold, seedling dry matter weight, seedling length ) tests to the field performance of nine corn seed lots in in three locations in the state of São Paulo, Brazil. These locations were Jaboticabal, Fernandópolis, and Piracicaba. The results showed the cold, accelerated aging, and the electrical conductivity were the best vigor tests to evaluate the performance of corn seed lots in the field. The seedling dry matter content tests showed very variable results and thus in need of further studies